Response of Muslims in Indonesia, particularly the Council of Indonesian Ulama (Majelis Ulama Indonesia) as well as Nahdlatul Ulama and Muhammadiyah, to the social discrimination against Muslim communities in France - Mardiah, Anne (Ampera: A Research Journal on Politics and Islamic Civilization, 2023)
A report by a global human rights organization, found that violations against Muslim groups in France were widespread and all the acts committed were based on the name of state security. The Universal Declaration of Human Rights was prepared by representatives of countries with different legal and cultural backgrounds from all regions of the world which was proclaimed by the United Nations General Assembly on December 10, 1948 in Paris, France. This declaration then signifies that fundamental human rights must be universally protected. In this research, researchers aim to find out what social discrimination has occurred against Muslim groups in France, and researchers also want to know what are the reactions of Muslims in Indonesia in general and their responses, especially Council of Indonesian Ulama (MUI) and Nahdhatul Ulama and Muhammadiyah as representatives of Muslims in Indonesia against social discrimination against Muslim groups in France by using a qualitative approach method whose data collection techniques are through internet-based research, literature studies, and interviews. In their research results, researchers found that Indonesian society in general, especially MUI, NU, and Muhammadiyah continue to guard against Islamophobia in France and France as the country where the rules regarding international human rights were declared still have a high rate of discrimination, especially against Muslim minority groups.